Strengths and Weaknesses of Combating Corruption in the Finnish Public Administration - Kangas, Alma Sofia (My University, 2008)
This study is categorized as a master's thesis and the subject deals with administrative ethics, especially administrative corruption in Finland. The goal of this study is to examine corruption as an ethical issue in Finnish public administration. From the perspective of public administration has Finland for several years now, been perceived as very democratic and anti-corrupt country among with other Nordic Countries. In this paper, corruption and ethical administration are studied from the standpoint of the administrative sciences. Public administration being a part of society naturally along with political, economical, judicial and cultural matters, is full of special questions, explanations and interpretations, which are all dealt in administrative sciences (Salminen 2004a:9; cf. Kangas 2001: 24, 306). The quality of the whole society trough all the special divisions of it interacts to the welfare level of the society. Good, ethical administration is one part of successful welfare state. The research problem of the study is focused on Finland and corruption. The meaning is to define the Finnish public sector’s internal strengths and weaknesses. What are the strengths and what are the weaknesses of Finnish society when the topic is administrative corruption? Through public values, Finnish administrative culture and anti-corruption mechanisms are special emphasis made and with interpretative approach the results are linked based on SWOT analysis to be either strength or weakness. Finland has a specific legislation on bribery, regulations on the access of the public information and the position of the civil servants is good. According to the study some assumptions were made in the beginning that the public values that are influencing to the corruption situation are the high morality and ethics, openness and transparency as well as efficiency. Such conclusions, which can be seen as strengths, were that in Finnish public administration there is generally a mix of differently categorized values; information society builds trust through openness; and increasing interest on public values and value change builds strong base to ethical development. On the other hand vagueness of conducts and practices can be seen as weakness. From the theory that was concerning administrative culture, came out as most important factors, the low hierarchical structure and self-independency, evident of value-led management and strong history based development. By studying these issues, came evident that the strengths of Finnish administration are; the participation to annual measuring of administration’s performance; the ethics of the population upholding the values of common good; financial benefit trough corruption is not temptation because of equal society; feeling of independence when public actions are done strictly and right. As a weakness, was that good administration and low corruption are seen as a self-evidence and understanding the diversity of corrupt actions can be little difficult. When anti-corruption mechanisms were discussed were the most important matters the citizen’s control channels, legislation of Finland and the Finnish free media. In terms of these issues, the strengths were promoting, preventing and watchdogging control systems, strong interest to develop the corruption legislation and regulation and the free media, which works as a effective ‘control tool’. As an opposite the application of legislation and regulations and sometimes doubtful quality of media’s publications were realized to be the weaknesses.
Keywords: administrative corruption; administrative ethics; ethical values; administrative culture; anti-corruption mechanisms; fi=Hallintotiede : julkisjohtamisen ohjelma|